Prevention And Control Of Cyber Crimes - Kaur, Dr. Navneet (IJRDO -Journal of Computer Science Engineering, 2016)
Computers and their use is a day-to-day activity of all the students, professionals,teachers, universities, and banks, supermarkets, in the entertainment field, in medicalprofession and also in higher education. The use of this weapon is spreading varywidely in all parts of our society. As every weapon has two ways of operation, one isgood and essential and the other is bad and not essential. Many times, whenever anew weapon is invented, many people use it unknowingly for the wrong purposei. Soto aware them and to make the proper use of the power of the newly invented weapon,laws are to be formulated and should be implemented.Cyber crime is a generic term that refers to all criminal activities done using themedium of computers, the Internet, cyber space and the worldwide web. There isn’treally a fixed definition for cyber crime. The Indian Law has not given any definitionto the term „cyber crime‟. In fact, the Indian Penal Code does not use the term „cybercrime‟ at any point even after its amendment by the Information Technology(amendment) Act 2008, the Indian Cyber law But “Cyber Security” means protectinginformation, equipment, devices computer, computer resource, communication deviceand information stored therein from unauthorized access, use, disclosure, disruption,modification or destruction.The word “cyber law” encompasses all the cases, statutes and constitutionalprovisions that affect persons and institutions who control the entry to cyber spaceprovide access to cyberspace, create the hardware and software which enable peopleto access cyberspace or use their own devices to go “online” and enter cyberspace. Insimple way we can say that cyber crime is unlawful acts wherein the computer iseither a tool or a target or both. Cyber crimes can involve criminal activities that aretraditional in nature, such as theft, fraud, forgery, defamation and mischief, all ofwhich are subject to the Indian Penal Code. The abuse of computers has also given